Is inequality all about the tails?: The Palma measure of income inequality. Issue 1 (February 2014) - Cobham, Alex; Sumner, Andy
<x xml:space="preserve">Abstract</x> The rich are different from us; so are the very poor. But in most countries most of us are in the middle. That leads to problems when you try to measure inequality. Alex Cobham and Andy Sumner have come up with a better way to show that some countries are more equal than others.